MEREKONSTRUKSI SISTEM HUKUM ADMINISTRASI MENUJU HUKUM YANG MELAYANI - Sri Nur Hari Susanto (Masalah-Masalah Hukum, 2015)
This research aims to reconstruct the legal system, especially state administrative law so that it can function as a law that can serve the public interest. Other objectives is to study conceptually harmonize laws and regulations relating to public service. The method used is a normative legal research, which explores the use of a conceptual approach. The results showed that the reconstruction of the administrative law which is oriented toward public service, it must first pay attention to the paradigm shift of the administration of the state itself. It is thus necessary to take measures to harmonize the legislation of sectoral public services based on the principles / legal principles that are generally accepted